Women writing and writing about women - Jacobus, Mary (Routledge library editions. Women, feminism and literature, 2012)
This innovative collection of contemporary essays in feminist literary criticism provides a spectrum of approaches and positions, united by their common focus on writing by and about women. Spanning the novel, poetry, drama, film and criticism, the contributors emphasise some of the problems of theory and practice posed by writing as a woman and by women's representation in literature. The subjects of individual essays range from the nineteenth and twentieth century novel to avant-garde film, and from Victorian women poets to Russian women poets of today. Drawing on discipli.